LabVIEW based automation to laser molecular beam epitaxy - Teo, Janice Qin Yun. (2009)
The continuous advancement of the microelectronic technology, particularly on the shrinking dimensions in CMOS and MOSFET devices, has spurred significant improvements in epitaxy techniques over the few decades. To develop a coherent epitaxy system for facilitating improved research works, a highly reliable and flexible measurement system, which allows effective delivery of experimental processes, has to be built. Laser molecular beam epitaxy is one of the most versatile thin film deposition techniques for oxide-based electronics. The laser molecular beam epitaxy system has been established and realized in the Sensors and Actuators Laboratory located in Nanyang Technological University, School of Electrical and Electronic Engineering. As it is becoming increasingly essential to analyze the growth and micro-structural properties of thin films, there is a need to develop a user-friendly software application program to realize a computer based automation to the laser molecular beam epitaxy system. Using LabVIEW graphical software, the Application Program is designed to provide the users with an automated platform to control the temperature of the substrate heating, as well as to configure the high energy laser setting conditions. In addition, the user is able to obtain useful data, such as the timing information, working temperature of the substrate and laser pulse count from the Application Program, which is essential for data analysis and quality control.